Unveiling the Phytopharmacological Potentials of Mesua nagassarium (Burm. f.): In vitro and In silico Approaches - Samadd, Md Abdus; Sikder, Md Al Amin; Asrafi, Sania; Hasan, Choudhury Mahmood; Al Mansur, Muhammad Abdullah; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2024)
This study focuses on the chemical, biological and computational studies of stem bark of Mesua nagassarium (Burm. f.). Using extensive chromatographic analyses, five compounds were isolated from the carbon tetrachloride soluble fraction of methanol extract of the plant. The isolated compounds were characterized as taraxerol (1), a mixture of β- amyrin (2) and α-amyrin (3), β-stigmasterol acetate (4) and kaempferol (5) by analysis of their spectral data, notably NMR. This is the first report of isolation of taraxerol and β-stigmasterol acetate from M. nagassarium. The n-hexane soluble materials of bark of M. nagassarium exhibited promising antioxidant (IC50 = 6.7 μg/ml) and cytotoxic (IC50 = 14.68 μg/ml) properties. In addition, the chloroform fraction showed mild thrombolytic activity with 26.27% clot lysis. The phytoconstituents were evaluated by molecular docking against superoxide dismutase, vascular endothelial growth factor receptor 2 and tissue plasminogen activator. Each compound had various degrees of binding affinity to the receptors. The results revealed strong cytotoxic and antioxidant effects of the extractives, underscoring the necessity for future research for isolating the bioactive phytochemicals against a variety of cellular targets. Dhaka Univ. J. Pharm. Sci. 23(2): 181-193, 2024 (December)